The Effect of Father and Child Bonding on Children’s Emotional Development Through Emotion Regulation as a Mediating Variable - Nurul Ida Rachmawati; Arsan Shanie (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
Emotional development is a crucial aspect of children’s growth during the elementary school phase. Children’s emotional development is influenced by various factors, one of which is the emotional bonding with the father. This study aimed to analyze the effect of father and child bonding on children’s emotional development through emotion regulation as a mediating variable. This study employed a quantitative correlational design involving 46 student cases as the primary unit of analysis, with 46 fathers and 3 teachers serving as triangulation sources. Questionnaires were used to gather data, which IBM SPSS 27 was used to analyze using multiple linear regression, path analysis, and the Sobel test. The results showed that father and child bonding significantly affected emotion regulation, and emotion regulation significantly affected emotional development. Emotion regulation significantly affected emotional development (β = 0.680, t = 4.410, p < 0.001), while father and child bonding did not directly affect emotional development (β = -0.341, p = 0.064) but showed a significant indirect effect through emotion regulation (z = 3.936), indicating full mediation. These findings highlight emotion regulation as a key mechanism linking father and child bonding to children’s emotional development. Therefore, parents, schools, and school counselors should strengthen children’s emotion regulation skills through collaborative parenting, emotional support programs, and school-based counseling interventions.